Genealogy and ethnomathematics: An approach in favor of the insurrection of subjugated knowledge Genealogia e Etnomatemática: uma aproximação em prol da insurreição dos saberes sujeitados - Junior V.D. (2014)
This study addresses the thought of Michel Foucault's genealogy for the Ethnomatematics. The genealogy problematizes what is considered true and seeks an insurrection of subjugated knowledge by a hegemonic scientific discourse. Based on this perspective, our main goal is to establish a dialogue between genealogy and Ethnomatematics in order to trace elements that make an insurrection of mathematics knowledge that have been subjugated by modern scientific discourse of mathematics, in the context of mathematics education. The dialogue between genealogy and Ethnomatematics allows us to problematize the acceptance of a universal mathematics that dictates what should be taught and, furthermore, makes possible for the appearance of different mathematics subjugated knowledge.